The Mediating Role of Emotional Regulation in the Relationship between Attachment Styles and Psychological Well-being - Akram Moradi Janati; Somaieh Salehi; Farnaz Shaygan Majd (Caspian Journal of Health Research, 2024)
Background: People with a high sense of psychological well-being mainly experience more positive emotions and have a positive evaluation of the incidents and events around them. Psychological well-being includes life satisfaction, emotional balance and general attitude towards optimism with a positive orientation towards life, so people's attachment style can play an effective role in promoting psychological well-being. Objective: The present study was conducted with the aim of determining the mediating role of emotional regulation in the relationship between attachment styles and psychological well-being. Materials & Methods: A total of 250 couples (125 male and 125 female) referred to Taranom Life Counseling Center and Atiyeh Counseling Center located in the 2nd district of Qazvin city were selected using convenience sampling method in the first quarter of 2022. The participants completed the psychological well-being scale, adult attachment styles, and emotional regulation questionnaire. Data were analyzed using Structural Equation Model (SEM) in AMOS software. Results: The results of this research showed that 79% of the variance of psychological well-being was explained by predictor variables. Secure attachment style has a significant positive correlation with psychological well-being. Anxious and avoidant attachment styles have a significant negative correlation with psychological well-being. The results of SEM showed that emotional regulation has a significant indirect effect (mediating role) on the relationship between attachment styles and psychological well-being. Conclusion: The study findings revealed that the emotional regulation plays a mediating role in the relationship between attachment styles and psychological well-being. It is suggested to strengthen the psychological well-being of couples by identifying attachment styles of couples and raising awareness in the field of emotional regulation.